Triterpenes and antitubercular activity of Byrsonima crassa - Higuchi, Célio Takashi [UNESP]; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Sannomiya, Miriam [UNESP]; Vilegas, Wagner [UNESP]; Leite, Sergio Roberto de Andrade [UNESP]; Sacramento, Luis Vitor S. [UNESP]; Sato, Daisy Nakamura (Sociedade Brasileira de Química, 2008)
We evaluated the potential antitubercular activity of triterpenes obtained from leaves and bark of Byrsonima crassa. From chloroform extracts of the leaves, by bioassay-guided fractionation, we obtained mixtures of known triterpenes: α-amyrin, β-amyrin and their acetates, lupeol, oleanolic acid, ursolic acid and α-amyrinone. Tested against Mycobacterium tuberculosis, the triterpenes exhibited minimum inhibitory concentrations (MICs) of 31.25 - 312.25 µg/mL. β-amyrin and friedelin, isolated from the chloroform extract of bark, showed MICs of 312.25 and 125 µg/mL respectively. This is the first report of the identification and determination of the activity of B. crassa triterpenes against M. tuberculosis.
Keywords: Byrsonima crassa; antitubercular activity; triterpenes